Use of Box–Behnken design for optimization of compounded medication: acyclovir capsules report - Suelen da Silva Reis; Valdemir da Silva Quintanilha Junior; Gabriella da Silva Boto; Thalita Martins da Silva; Elizabeth Valverde Macedo; Carlos Augusto de Freitas Peregrino; Samanta Cardozo Mourão; Emeli Moura de Araújo (Drug Analytical Research, 2021)
Campus compounding pharmacies play an important role in public health. Herpes simplex is one of the most common viral diseases in humans, which generates a great demand for acyclovir capsules in compounding pharmacy. It is well known that the formulation's components influence the effectiveness of the drug. The objective of this study is to show the applicability of Box-Behnken design in optimization of a compounded formulation and to evaluate the effect of excipients on dissolution and drug content in acyclovir 200 mg capsules produced at UFF´s University Pharmacy (FAU). The formulations were prepared and evaluated for average weight test, uniformity of dosage units and in vitro dissolution, while meeting pharmacopoeial specifications. A statistical analysis showed that sodium starch glycolate, Aerosil®, influences drug content and dissolution results. Magnesium stearate shows no influence on the dissolution at different concentrations but influences the assay results. A numerical optimization was applied to adjust the formulation variables based on the foresaid responses, accomplishing the best formulation that will be prepared and dispensed at FAU upon medical prescription.